LINGVOPOETIC FEATURES OF THE AUTHOR’S IDIOSTYLE (Scientific journal of the Fergana State University, 2026)
This article presents theoretical views on the study of the author’s idiostyle, which represents one of the central issues in poetic syntax. In studies devoted to the linguopoetic analysis of literary works, idiostyle is defined as a complex system of linguistic devices and means that serve to reveal the author’s artistic world. This definition demonstrates that the author subordinates linguistic regularities unique to their own creative manner in word choice and thought expression. As a linguistic term, idiostyle is a shortened form of “individual style” and refers to a specific stylistic complex encompassing an author’s distinctive features of language use. The term is employed in linguistic and literary studies to describe the inimitable and unique manner of expression, word choice, and communication that differentiates one author’s style from another. Within the framework of Uzbek poetic syntax, based on global linguistic experience, the importance of studying the author’s idiostyle as a separate category in the analysis of Uzbek poetic speech is emphasized.